MENINGKATKAN KETERAMPILAN BERBICARA DAN PERCAYA DIRI SISWA MELALUI PENERAPAN MODEL EVERYONE IS A TEACHER HERE (ETH) - Aigadilla Anugrah; Mara Untung Ritonga; Wisman Hadi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Enhancing students' speaking skills specifically in expressing opinions, engaging in discussions, and delivering presentations requires innovative approaches in schools. This study aims to assess the improvement in students' speaking abilities and self-confidence through the implementation of the Everyone Is A Teacher Here (ETH) learning model in Class VC at SD Negeri 105855 PTPN II Tanjung Morawa. The research employs a descriptive qualitative method to analyze the phenomena occurring within the study's context. Data collection techniques included observation, interviews, and document analysis. The findings indicate that the implementation of the ETH model has a positive impact, evidenced by the following outcomes: (1) students demonstrate effective collaboration, (2) students formulate relevant questions related to the learning material, and (3) students exhibit the courage to perform in front of the class and respond to inquiries from other groups. This model significantly enhances students' learning outcomes, fostering increased activity and enthusiasm during the learning process, as the employed strategies effectively engage their interest. Consequently, the Everyone Is A Teacher Here (ETH) model has received positive feedback from students and is recommended for application by educators.